2013
DOI: 10.1182/blood-2013-03-492884
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of primary myelodysplastic syndromes in adults: recommendations from the European LeukemiaNet

Abstract: Within the myelodysplastic syndrome (MDS) work package of the European LeukemiaNet, an Expert Panel was selected according to the framework elements of the National Institutes of Health Consensus Development Program. A systematic review of the literature was performed that included indexed original papers, indexed reviews and educational papers, and abstracts of conference proceedings. Guidelines were developed on the basis of a list of patient- and therapy-oriented questions, and recommendations were formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
563
2
29

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 598 publications
(606 citation statements)
references
References 262 publications
12
563
2
29
Order By: Relevance
“…As observed in numerous previous studies, 23,[51][52][53][54][55][56] OS was found to be slightly lower in patients ⩾ 55 years without reaching any statistical significance in uni-and multivariate analysis. However, of greater clinical interest is that (1) the documented difference was so small that neither univariate nor multivariate analysis could reveal a significant impact of patient age on OS; and (2) stable plateaus for OS were reached for both subgroups, suggesting potential cure rates of 50% for younger and 42% for elderly patients (cf.…”
Section: Discussionsupporting
confidence: 59%
“…As observed in numerous previous studies, 23,[51][52][53][54][55][56] OS was found to be slightly lower in patients ⩾ 55 years without reaching any statistical significance in uni-and multivariate analysis. However, of greater clinical interest is that (1) the documented difference was so small that neither univariate nor multivariate analysis could reveal a significant impact of patient age on OS; and (2) stable plateaus for OS were reached for both subgroups, suggesting potential cure rates of 50% for younger and 42% for elderly patients (cf.…”
Section: Discussionsupporting
confidence: 59%
“…Guidelines on ICT in MDS are often included in guidelines on MDS treatment in general. For example, the European LeukemiaNet Guideline on the diagnosis and treatment of primary MDS in adults includes a short segment on ICT [45], suggesting that this treatment should be considered in transfusion-dependent patients with RA, RARS, or MDS with isolated 5q deletion and a serum ferritin level higher than 1000 ng/mL after approximately 25 units of red cells. In addition, MDS patients who are potential candidates for allo-SCT can be considered for appropriate iron chelation therapy prior to the conditioning regimen for transplantation.…”
Section: Treatment Of Iron Overload In Patients With Mdsmentioning
confidence: 99%
“…1 The authors provide encouraging data from both a leukemic mouse model and a single CML-AP patient, corroborating mechanistic studies suggesting that KPT-330 efficacy relies on targeting abundantly expressed XPO1, followed by the reactivation of protein phosphatase 2A (PP2A). N ormal cellular homeostasis depends on the cell's ability to compartmentalize proteins within specific subcellular compartments.…”
mentioning
confidence: 53%